How Does AI Improve Patient Recruitment for Clinical Trials? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Clinical trials are the bedrock of medical innovation, yet they consistently face a significant hurdle: patient recruitment. The process is often slow, expen...
Keywords: Drug Discovery and Pharmaceutical AI; Improve; Patient; Recruitment; Artificial Intelligence; Machine Learning